Experiences with implementation of continuous positive airway pressure for neonates and infants in low-resource settings: A scoping review. - Sara Dada; Henry Ashworth; Alina Sobitschka; Vanitha Raguveer; Rupam Sharma; Rebecca L Hamilton; Thomas Burke (PLoS ONE)
Background Continuous positive airway pressure (CPAP) is the gold standard of care in providing non-invasive positive pressure support to neonates in respiratory distress in high-resource settings. While safety has been demonstrated in low-resource settings, there is a lack of knowledge on the barriers and facilitators to proper implementation. Objective To identify and describe the barriers, facilitators, and priorities for future implementation of CPAP for neonates and infants in low-resource settings. Methods A systematic search (database inception to March 6, 2020) was performed on MEDLINE, Embase, Web of Science, CINAHL, Global Health, and the WHO Global Index Medicus using PRISMA-ScR guidelines. Original research articles pertaining to implementation of CPAP devices in low-resource settings, provider or parent perspectives and experiences with CPAP, cost-benefit analyses, and cost-effectiveness studies were included. Inductive content analysis was conducted. Findings 1385 article were screened and 54 studies across 19 countries met inclusion criteria. Six major themes emerged: device attributes, patient experiences, parent experiences, provider experiences, barriers, and facilitators. Nasal trauma was the most commonly reported complication. Barriers included unreliable electricity and lack of bioengineering support. Facilitators included training, mentorship and empowerment of healthcare providers. Device design, supply chain infrastructure, and training models were imperative to the adoption and sustainability of CPAP. Conclusion Sustainable implementation of CPAP in low resource settings requires easy-to-use devices, ready access to consumables, and holistic, user-driven training. Further research is necessary on standardizing metrics, interventions that support optimal provider performance, and conditions needed for successful long-term health system integration.